2011
DOI: 10.1037/a0025416
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fictional Narrative Experience on Work Outcomes: A Conceptual Analysis and Research Model

Abstract: Fictional narrative experience is assumed to have a profound impact on human behavior, but the possible outcomes and the processes through which fictional narrative experience influence behaviors have rarely been studied. This paper introduces a model of the consequences of fictional narrative experience through transportation and transformation processes. We discuss a framework for understanding the effects of fictional narrative experience, distinguishing affective and behavioral effects, and temporality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…When a reader is not able to identify with a fictional narrative and does not become transported, this might lead to disengagement, with the reader being distracted and frustrated. When readers disengage from what they read, they possibly become more self-centered and selfish in order to protect the sense of self in relation to others [17]. Yet, these results are important, because previous research has claimed that fiction reading has positive effects [6][7], while we are amongst the first who also show that fiction reading might have negative effects, when readers do not become transported, and hence, disengage from literature.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…When a reader is not able to identify with a fictional narrative and does not become transported, this might lead to disengagement, with the reader being distracted and frustrated. When readers disengage from what they read, they possibly become more self-centered and selfish in order to protect the sense of self in relation to others [17]. Yet, these results are important, because previous research has claimed that fiction reading has positive effects [6][7], while we are amongst the first who also show that fiction reading might have negative effects, when readers do not become transported, and hence, disengage from literature.…”
Section: Discussionmentioning
confidence: 70%
“…First, and most importantly, the current study followed the transportation framework of Gerrig [12], [17] to postulate specific predictions of the conditions under which fiction experience relates to outcomes. We have shown that emotional transportation influences the reactions toward fiction reading in terms of changes in empathy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may have important implications for the potential of using literature in specific environments, for example, teachers' professional development (Kooy, 2006), people's professional behavior in general (Bal, Butterman & Bakker, 2011), and domainspecific education in literary studies (e.g., Fialho, Zyngier & Miall, 2011;Fialho, Miall & Zyngier, 2012) as well as the secondary literature classroom that forms the context for the present study.…”
Section: Reading Literary Fiction: Changes In Self and Social Perceptmentioning
confidence: 99%